Reproducible and acid‐responsive Rhodamine B/PEG functioned nanographene oxide‐Au nanocomposites for surface‐enhanced Raman scattering sensing - Wenhao Qian; Min Xing; Mao Ye; Xiaoyu Huang; Yongjun Li; Bingjie Hao (SmartMat)
Abstract Surface‐enhanced Raman scattering (SERS) has been visualized as a promising analytical technique in marked‐molecule detection for disease diagnosis, environmental pollution, and so on. Noble metal nanoparticles, especially gold nanoparticles (AuNPs), are commonly used to fabricate SERS substrates. Herein, we facilely fabricated a special platform to improve the dispersity and homogeneity of AuNPs. Practically, based on nano‐graphene oxide (GO), a special platform (s‐GO‐PEG‐R'hB) was prepared through GO functionalization with biocompatible poly(ethylene glycol) (PEG), acid‐activated fluorescence molecule (Rhodamine B lactam derivative, R'hB) and thiol sites with cysteamine. AuNPs were then in situ grown on s‐GO‐PEG‐R'hB sheets to provide GO/AuNPs nanocomposite (Au@s‐GO‐PEG‐R'hB) for use as an efficient SERS substrate, which can exert unique electromagnetic characteristics of AuNPs and improve its dispersity. With systematic morphology and composition characterizations, it was confirmed that uniform AuNPs were located on multi‐functionalized GO sheets in Au@s‐GO‐PEG‐R'hB as we designed. Au@s‐GO‐PEG‐R'hB performed well in SERS detection towards 4‐aminothiophenol (4‐ATP) and p‐phenylenediamine (PD), with preferable sensibility, stability and effectiveness. With well‐knit SERS results, it is indicated that Au@s‐GO‐PEG‐R'hB could take the advantages of inherent electrochemical properties of AuNPs and functionalized GO to be a potential substrate in SERS detection. Thus, it is foreseen that Au@s‐GO‐PEG‐R'hB can meet diverse SERS sensing demands in real life.